Bilaterally positive head-impulse tests can differentiate AICA infarction from labyrinthitis - Kim, Sung-Hwan; Kim, Hanseob; Lee, Sun-Uk; Park, Euyhyun; Cho, Bang-Hoon; Cho, Kyung-Hee; Kim, Gerard J.; Yu, Sungwook; Kim, Ji-Soo (Frontiers in Neurology, 2024)
Introduction Video head-impulse tests (video-HITs) often fail to detect anterior inferior cerebellar artery (AICA) infarction due to peripheral and central vestibular system involvement. Anecdotal studies suggest that video-HITs may reveal bilateral impairment in AICA infarction. However, the diagnostic utility of video-HITs has not been established, particularly when compared to labyrinthitis, which accounts for the majority of acute audiovestibular syndrome (AAVS) cases. Methods We reviewed the medical records of consecutive patients presenting with new-onset acute hearing loss and spontaneous vertigo (i.e., AAVS) between March 2018 and July 2023 at a tertiary hospital in South Korea. Video-HIT patterns were categorized as follows: (1) ipsilaterally positive, (2) contralaterally positive, (3) bilaterally normal, and (4) bilaterally positive. Results Twenty-eight patients with AICA infarction (mean age±standard deviation = 67±15 years; 14 men) and 51 with labyrinthitis (63±17 years, 26 men) were included in the analyses. Among the 28 patients with AICA infarction, 15 presented with AAVS in isolation, without other co-morbid neurologic deficits (15/28, 54%). The vestibulo-ocular reflex (VOR) gains of ipsilesional horizontal canals (HCs) ranged from 0.21 to 1.22 (median = 0.81, interquartile range [IQR] = 0.50–0.89). However, those for contralateral HC gain ranged from 0.57 to 1.19 (median = 0.89 [IQR = 0.73–0.97]). Collectively, HITs were bilaterally positive in 13 patients (including 12 patients with bilaterally positive HITs for the horizontal canal), normal in eight, ipsilesionally positive in six, and contralesionally positive in one patient with AICA infarction. The VOR gains were typically decreased ipsilaterally in 28 (28/51, 55%), normal in 17 (17/51, 33%), and decreased bilaterally in six patients with labyrinthitis (6/51, 12%). Logistic regression analysis revealed that bilaterally positive HITs (p = 0.004) and multiple vascular risk factors (p = 0.043) were more frequently associated with AICA infarction than labyrinthitis. Discussion Among patients presenting with AAVS, bilaterally positive HITs can be indicative of AICA infarction in patients with multiple vascular risk factors.